Organisational politics: the role of justice, trust and job ambiguity - Othman, Rozhan (Singapore Institute of Management, 2008)
Studies on organisational politics have identified a number of antecedents of perception of organisational politics. One variable that has generated some interest as an antecdent of perception of organisational politics is justice. However, there have been limited studies of this relationship. This paper posits that the lack of justice can create a perception of organisational politics. It is argued that the lack of justice undermines trust and subsequently leads to political behaviour. This study examines how justice is related to other antecedents of perception of organisational. politics and how this relationship affects intention to quit. Using data from a firm in a turnaround process, this study found evidence to support the hypotheses proposed.